Design of a Web-based Production and Sales Management Information System for the Small Business Convection Industry - Alfabian Akbar; Dimas Ardhana (PT. Altaf Publishing Corp, 2025)
This research aims to develop a web-based information system to overcome production and sales management problems in the small-scale convection industry. The main challenge identified is the lack of operational efficiency due to manual record-keeping, which frequently leads to data discrepancies in stock management, order tracking, and production scheduling. To address these issues, this study designs a centralized management information system featuring raw material inventory control, customer order processing, production monitoring, and automated sales reporting. The system was developed using the Waterfall methodology, ensuring a structured development lifecycle from requirement analysis to functional implementation. The results demonstrate a significant increase in operational efficiency through real-time stock monitoring and accelerated order processing. Functional validation using the Black-box testing method confirms that all system features operate correctly and align with the business requirements. This digital transformation provides a scalable solution for convection SMEs to minimize human error and enhance data-driven decision-making in a competitive market environment.